Pengaruh Pemberian Pupuk Organik Cair Hasil Fermentasi Buah Maja dan Pupuk Organik Cair NASA Terhadap Pertumbuhan Tanaman Tomat (Lycopersicum esculentum) : Comparison of Application of Liquid Organic Fertilizer Fermentation of Maja Fruit and NASA Liquid Organic Fertilizer on Tomato Plant Growth (Lycopersicum esculentum) - Kamilia, Wardah; Laili, Saimul; Tito, Sama' Iradat (Jurnal SAINS ALAMI (Known Nature), 2023)
Tomato (Lycopersicum esculentum) is a multipurpose and multifunctional fruit vegetable that can be cultivated in lowland or highland land. One of the factors that greatly affect the yield of tomato plants is fertilization. Liquid organic fertilizer fermented maja fruit is a simple fertilizer extracted from maja fruit, liquid organic fertilizer fermented maja fruit can provide additional organic matter in the form of nutrients needed by plants. NASA liquid organic fertilizer is a liquid organic fertilizer which is an extraordinary invention in the world of agriculture and can provide nutrients to plants. This research was conducted in the garden of Jalan Joyo Suryo, Merjosari, Kec. Lowokwaru, Malang City in June â€“ August 2021. The results showed that the best in the study was the administration of NASA liquid organic fertilizer with a concentration of 20 ml due to the availability of macro and micro nutrients which were more complete and easily absorbed than the liquid organic fertilizer fermented by maja fruit. which also has lower effectiveness at 5ml concentration. Keywords: Maja Fermentation liquid organic fertilizer, NASA liquid organic fertilizer, Tomato ABSTRAK Tomat (Lycopersicum esculentum) tergolong sayuran buah multiguna dan multifungsi yang dapat dibudidayakan di lahan dataran rendah ataupun lahan dataran tinggi. Salah satu faktor yang sangat mempengaruhi hasil tanaman tomat adalah pemupukan. Pupuk organik cair hasil fermentasi buah maja merupakan pupuk sederhana yang diekstraksi dari buah maja, pupuk organik cair hasil fermentasi buah maja dapat memberi tambahan bahan organik berupa unsur hara yang diperlukan tanaman. Pupuk organik cair NASA adalah pupuk organik cair yang merupakan penemuan yang luar biasa dalam dunia pertanian serta dapat memenuhi nutrisi pada tanaman. Penelitian  ini dilaksanakan di kebun Jalan Joyo Suryo, Merjosari, Kec. Lowokwaru, Kota Malang pada bulan Juni – Agustus 2021. Hasil penelitian menunjukkan yang terbaik dalam penelitian yaitu pada pemberian pupuk organik cair NASA konsentrasi 20ml karena ketersediaan unsur hara makro dan mikro yang lebih lengkap dan mudah  terserap dengan baik dibanding pupuk organik cair hasil fermentasi buah maja yang juga memiliki efektivitas lebih rendah dengan konsentrasi 5ml.  Kata kunci: POC Maja, POC NASA, Tomat